Marketing Channels of Pomegranate in Pune Division of Maharashtra, India - , Umesh D. Tamboli, Mahesh R. Prajapati (Archives of Current Research International, 2024)
Pomegranate, scientifically named Punica granatum L., is prized globally, particularly in tropical and subtropical regions like India, Iran, and Spain. Pomegranate cultivation has surged in India, notably in Maharashtra, Gujarat, and Karnataka, with India emerging as a top global producer. In 2020-21, India expanded pomegranate cultivation to 2.88 lakh hectares, yielding 32.70 lakh tonnes. Maharashtra led with 54.89% of national production and 59.38% of cultivated area, underscoring its key role despite slightly lower productivity than the national average. The objectives of the study were to identify different marketing channels of pomegranate, to estimate the price spread and marketing efficiency of identified marketing channels and to identify problems faced by stakeholders. The primary data was collected from 60 Pomegranate farmers and from 30 intermediaries. The study identified four different pomegranate marketing channels. Channel-1 (Producer →Pre-harvest contractor → Wholesaler-cum-commission agent→ Retailer →Consumer), Channel-2 (Producer →Wholesaler-cum-commission agent→ retailer → consumer), Channel-3 (Producer →Collection Center (CC) → Distribution Center (DC) → Consumer), Channel-4 (Producer →Village trader →Wholesaler-cum-commission agent →Retailer → Consumer). Channel-3 providing producers with 69.78% of the consumer price and demonstrating highest efficiency (2.31) for its Acharya-Agarwal marketing efficiency method was used. Pomegranate producers face challenges including high transportation costs, storage issues, price volatility, and market information deficits. Production problems include pest infestations, high input costs, and labor shortages. Intermediaries grapple with quality variation, labor scarcity, and price fluctuations. Strategic interventions in infrastructure, logistics, and market intelligence are crucial for sustainable profitability.